2018
DOI: 10.1021/acs.jpcc.8b03142
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Approach Toward the Adsorption of Molecular Hydrogen as Well as the Formation of Metal Hydride on Bare and Activated Carbon-Supported Rhodium Clusters

Abstract: A systematic density functional theory (DFT) investigation has been performed to understand adsorption phenomenon as well as the mechanism of hydrogen molecule dissociation to form metal hydride, catalyzed by bare and activated carbon-supported small rhodium clusters. H–H bond length of hydrogen molecule adsorbed on activated carbon-supported rhodium cluster is found to be higher. Five- as well as six-member rings of the activated carbon act as the support for hydrogen-adsorbed rhodium clusters. Rhodium cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 49 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…In the same work, it Even if theoretically, activated carbon or carbon black (CB) have been less studied, due to the large size of these systems, we can mention the work of Dutta et al They have systematically investigated by DFT calculations performed on a curved polyaromatic hydrogenated (PAH) molecule, used as a model of activated carbon surface, the mechanism of dihydrogen molecule dissociation to form metal hydride on supported small rhodium clusters, catalyzed by bare and activated carbon. 97 Five-as well as six-member rings of the activated carbon act as the support for hydrogen-adsorbed rhodium clusters. When a rhodium cluster is linked with a five-member ring of activated carbon, it has the enhanced ability to activate H2 molecule.…”
Section: D Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same work, it Even if theoretically, activated carbon or carbon black (CB) have been less studied, due to the large size of these systems, we can mention the work of Dutta et al They have systematically investigated by DFT calculations performed on a curved polyaromatic hydrogenated (PAH) molecule, used as a model of activated carbon surface, the mechanism of dihydrogen molecule dissociation to form metal hydride on supported small rhodium clusters, catalyzed by bare and activated carbon. 97 Five-as well as six-member rings of the activated carbon act as the support for hydrogen-adsorbed rhodium clusters. When a rhodium cluster is linked with a five-member ring of activated carbon, it has the enhanced ability to activate H2 molecule.…”
Section: D Materialsmentioning
confidence: 99%
“…1041 The first step in H-spillover on TM particles is to dissociate hydrogen molecules. Although several metals or semi-metals have been investigated (Ni, 349,1031 Ti, 349,556,1042 V, 1043 Rh, 97,556 Cu, 1044 kcal.mol -1 at full coverage, and 74 kcal.mol -1 at zero coverage. 989 On carbon supported Pt4 clusters, the dissociative chemisorption of H2 is barrierless, up to saturation (5 to 6 H2).…”
Section: Hydrogen Spillovermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a bridging hydride resembling that in 11 has been proposed and calculated in both rhodium-based homogeneous bimetallic28 and heterogeneous systems 26. This observation further underlines the utility of low valent homobimetallic complexes with ligands containing alkene and alkyne binding sites in understanding elementary steps in heterogeneous catalysts which are deposited on carbon support materials.…”
Section: Resultsmentioning
confidence: 54%
“…But the mode of interaction between the supported rhodium sites and H 2 is not fully understood 25. A recent DFT study reported that hydrogen activation by small rhodium clusters on a carbon support features a bridging hydride species and a hydride ligand (Scheme 1a) that could be transfered to the carbon support 26. However, such intermediates have not been observed experimentally to date.…”
Section: Introductionmentioning
confidence: 99%